The Obstacles Faced by University Students in Learning English Language - Parwn Othman Mustafa (QALAAI ZANIST SCIENTIFIC JOURNAL, 2020)
This study is entitled (the obstacles faced by university Students in Learning English Language). It addresses the obstacles that are faced by the students in the Faculty of Arts at Soran University in Learning English Language which is one of the live languages that is relied upon as a formal language all over the international and world organizations and offices. The main aim of this study is to determine and analyse the obstacles that are faced by the students in the Faculty of Arts at Soran University. This study adopts a descriptive- statistical method within quantitative approach. This approach is based on close-ended data such as yes, no question or multiple choice questions. This and similar studies make use of data analysis programs such as SPSS. The data was collected from 26 (13 male and 13 female) students. The results reveal that there are a number of obstacles such as lack of learning tools, lack of an appropriate method of teaching, syllabus and the students desire to learn the language. The results also show that the girls face more obstacles in learning the language compared to boys